Improving Surgical Resection of Metastatic Liver Tumors With Near-Infrared Optical-Guided Fluorescence Imaging. (August 2016) - Barabino, Gabriele; Porcheron, Jack; Cottier, Michèle; Cuilleron, Muriel; Coutard, Jean-Guillaume; Berger, Michel; Molliex, Serge; Beauchesne, Brigitte; Phelip, Jean Marc; Grichine, Alexei; Coll, Jean-Luc
Objective . The aim of this study was to investigate the feasibility and future clinical applications of near-infrared (NIR) fluorescence imaging to guide liver resection surgery for metastatic cancer to improve resection margins. Summary Background Data . A subset of patients with metastatic hepatic tumors can be cured by surgery. The degree of long-term and disease-free survival is related to the quality of surgery, with the best resection defined as "R0" (complete removal of all tumor cells, as evidenced by microscopic examination of the margins). Although intraoperative ultrasonography can evaluate the surgical margins, surgeons need a new tool to perfect the surgical outcome. Methods . A preliminary study was performed on 3 patients. We used NIR imaging postoperatively "ex vivo" on the resected liver tissue. The liver tumors were preoperatively labelled by intravenously injecting the patient with indocyanine green (ICG), a NIR fluorescent agent (24 hours before surgery, 0.25 mg/kg). Fluorescent images were obtained using a miniaturized fluorescence imaging system (FluoStic, Fluoptics, Grenoble, France). Results . After liver resection, the surgical specimens from each patient were sliced into 10-mm sections in the operating room and analyzed with the FluoStic. All metastatic tumors presented rim-type fluorescence. Two specimens had incomplete rim fluorescence. The pathologist confirmed the presence of R1 margins (microscopic residual resection), even though the ultrasonographic analysis indicated that the result was R0. Conclusions . Surgical liver resection guided by NIR fluorescence can help detect potentially uncertain anatomical areas that may be missed by preoperative imaging and by ultrasonography during surgery. These preliminary results will need to be confirmed in a larger prospective patient series.